In situ scanning electron microscopy-based high-temperature deformation measurement of nickel-based single crystal superalloy up to 800 °C. (September 2018) - Liang, Jiecun; Wang, Zhen; Xie, Hongfu; Li, Xide
Highlights: Figure out the main reason that causes imaging failure exceed 700 °C of SS-550 type SHIMADZU in-situ high-temperature SEM. Increase the in-situ imaging-temperature from 650 °C to 800 °C by a modified contact heating method. Find the optimal reverse voltage to increase the signal-to-noise ratio at high temperature. Develop a stable speckle pattern for high temperature deformation measurement in SEM. Abstract: In situ observation and measurement of high-temperature deformation of hot-section materials in scanning environments is helpful in understanding the microscopic failure and fracture mechanisms of these materials and estimating their safe life cycles. However, in situ high-temperature measurements in a scanning electron microscopy (SEM) environment pose major challenges in high-efficiency heat source design, establishment of stable high-contrast microscopic images, and quantitative measurement of the deformation fields in the high-temperature environment. New methods and approaches must be therefore developed for quantitative measurement of these high-temperature mechanical properties. This article reports use of in situ SEM to measure the high-temperature deformation and fatigue properties of a nickel-based single crystal superalloy (NBSCS) up to 800 °C. A conductive heating source has been constructed based on numerical calculations of the thermal field inside the SEM chamber and analysis of the secondary electron spectrum and thermionic emissions received by the detector. Al2 O3 nano-scale particles were coated on the NBSCS surfaces and were used to form speckle patterns to measure the deformation of NBSCS from room temperature up to 800 °C via a digital image correlation technique. The stable spatial geometric configuration and enhanced interfacial strength between the Al2 O3 particles and the sample surface with increasing temperature validate the developed high-temperature speckle patterns. Tensile and fatigue experiments are performed for NBSCS samples using the developed system. Full-field displacements are obtained near the notch root and in situ fatigue crack propagation is reported in the temperature range from 600 °C to 800 °C.